Semiparametric Spline Truncated Regression on Modelling AHH in Indonesia - Fitriana, Dewi; Budiantara, I Nyoman; Ratnasari, Vita (Institut Teknologi Sepuluh Nopember, 2018)
Life expectancy (AHH) is an indicator that can reflect the health status of a region, whether from infrastructure, access, and health quality. As one of the dimensions of the Human Development Index (HDI), AHH is deemed to need global attention. Today, AHH growth in developing countries is slow even slower when compared to underdeveloped countries. In Indonesia, the trend of life expectancy at birth continues to increase, but the achievement of national AHH is still lagging behind the AHH of neighboring countries. In addition, as an archipelagic country, the achievement of AHH among provinces still shows a disparity.This study modeled the factors that determine AHH with semiparametric spline truncated regression approach. The method of selecting optimum knots using Generalized Cross Validation (GCV) method. The best model that is formed is a model using three knots with the coefficient of determination of 84.70 percent. Significant variables were percentage of the poor population, percentage of households using clean drinking water, percentage of population who have health complaints, the percentage of under five years who have been complete immunized, and Mean Years of Schooling (MYS). The results of this study are expected to be an input for the Government to take policy in order to improve the national AHH as a whole